Wages anatomy: Labor supply of nurses and a comparison with physicians - Leif Andreassen; Maria Laura Di Tommaso; Steinar Strøm (University of Oslo, Department of Economics, 2014)
We estimate a dynamic discrete choice model of Registered Nurses' labor supply with random terms. A distinguished feature of our model is that random terms are correlated over time and jobs (habit persistence). Past options and not only the past optimal choices matter for the current choices. Given observed incentives, we find that nurses are mobile when they are young (less than physicians), but there is also a weak tendency of higher mobility again when they are approaching retirement age. Wage increases have a modest impact on labor supply. The overall elasticity for nurses is close to zero (like for physicians). These low elasticities shadow for stronger responses, shifting labor away from part time jobs in the public and private sector towards full time jobs in the private sector. A change in taxation away from the progressive tax system towards a flat tax of 28% gives Registered Nurses a very modest incentive to shift their job to private hospitals. For physicians the impact is stronger.
Keywords: J22; I10; C35; 330; nurses' labor supply; multi-sector; panel data